(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Stage organization including its physical structure, spatial arrangement and even the audiences organization has had a profound effect on the career of playwriting throughout history. The development of the techniques and forms of the dramatic literature is the obvious result of the stage details evolving. The successive civilizations of humanity throughout history give the stage development a great deal of importance to reflect their vision and lifestyle of their time. we can find different kinds of the theaters which differentiate certain civilization from others by its unique style. Greek. Roman and English theaters are the greatest throughout history. This study will follow up the theater stage organization development which affect the playwrights viewpoints and thoughts in these civilizations.